IMPLEMENTASI MANAJEMEN RISIKO TERHADAP PROFITABILITAS PADA BANK UMUM BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2019 - Muhamad Mardiansyah; Dewi Suryani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
Banks in achieving their profitability will certainly be faced with various risks, risk management is a logical and schematic method in identifying, quantifying, determining attitudes, determining solutions, and monitoring and reporting risks that occur in each bank business activity. The purpose of this study is to determine the influence of credit risk (NPL) and market risk (NIM) on bank profitability (ROA). This research is conducted at state-owned commercial banks listed on the IDX for the period 2010-2019. The method used in this research is quantitative and the source of the data in this study is obtained from secondary data with a sample size of 4 banking companies, namely Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Tabungan Negara and Bank Mandiri. The results of this study indicate that the credit risk free variable (NPL) has a negative but significant influence. The market risk variable (NIM) has a positive and significant influence on profitability with a regression coefficient value of 0.466 with a significant level of 0.000. The coefficient of determination shows that the contribution of the influence of the variable credit risk (NPL) and market risk (NIM) to profitability (ROA) is 87.3%, while the remaining 12.7% is influenced by other factors that are not included in the regression model.